2021
DOI: 10.1038/s41467-021-25568-6
|View full text |Cite
|
Sign up to set email alerts
|

Binding of regulatory proteins to nucleosomes is modulated by dynamic histone tails

Abstract: Little is known about the roles of histone tails in modulating nucleosomal DNA accessibility and its recognition by other macromolecules. Here we generate extensive atomic level conformational ensembles of histone tails in the context of the full nucleosome, totaling 65 microseconds of molecular dynamics simulations. We observe rapid conformational transitions between tail bound and unbound states, and characterize kinetic and thermodynamic properties of histone tail-DNA interactions. Different histone types e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
83
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(111 citation statements)
references
References 76 publications
9
83
1
Order By: Relevance
“…In addition, recent studies have reported that NMR signals of the H4 N-tail in the NCP are nearly identical to those of the free isolated peptide ( Rabdano et al., 2021 ). According to MD simulation, the H4 N-tail can search a large surface area from superhelical location (SHL) +2 to SHL –2 on nucleosomal DNA in the NCP and the nucleosome ( Rabdano et al., 2021 ; Peng et al., 2021 ). In the crystal structure of the NCP, weak electron density of the H4 N-tail is observed toward both SHL +2 (outward) and SHL –2 (inward) ( Arimura et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, recent studies have reported that NMR signals of the H4 N-tail in the NCP are nearly identical to those of the free isolated peptide ( Rabdano et al., 2021 ). According to MD simulation, the H4 N-tail can search a large surface area from superhelical location (SHL) +2 to SHL –2 on nucleosomal DNA in the NCP and the nucleosome ( Rabdano et al., 2021 ; Peng et al., 2021 ). In the crystal structure of the NCP, weak electron density of the H4 N-tail is observed toward both SHL +2 (outward) and SHL –2 (inward) ( Arimura et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…H2A N-tails bind to nucleosomal DNA at SHL ±4, whereas H2B N-tails are mostly bound at SHL ±3 and SHL ±5 ( Peng et al., 2021 ). Thus, it is possible that H2B N-tails compete with H3 N-tails on the nucleosomal DNA gyres.…”
Section: Discussionmentioning
confidence: 99%
“…Previous MD simulations revealed that histone tails can adopt many conformations 25 , 30 , 61 . Such MD simulations have been often performed below the microsecond timescale, which produces an averaged NMR signal for each amino acid atom.…”
Section: Discussionmentioning
confidence: 99%
“…The histone tails are responsible for nucleosomal stability 17 , inter-nucleosomal interaction 18 , DNA unwrapping 19 , nucleosome sliding 20 , 21 , and protein accessibility 22 25 . Specific residues of the histone tails are known to be targets for post-translational modifications, which act as epigenetic markers to regulate chromatin accessibility and gene expression 5 , 26 30 . However, characterizing the structural ensembles of histone tails at atomic resolution is difficult because of their conformational flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous biochemical and structural studies established the dynamic nature of the nucleosome in terms of its conformation and composition. The disordered N-terminal tail of histones have an affinity to DNA, forming a dynamic complex with DNA termed as “fuzzy conformational ensembles,” which regulate the chromatin structure and dynamics ( Ghoneim, Fuchs, and Musselman 2021 ; Peng et al, 2021 ; Shukla, Agarwal, and Kumar 2022 ). Polach and Widom, (1995) demonstrated the phenomenon of intrinsic structural dynamics of nucleosome known as “DNA breathing,” i.e., partially unwrapping and rewrapping of DNA spontaneously.…”
Section: Introductionmentioning
confidence: 99%